THE INFLUENCE OF BRAND AMBASSADORS, PRODUCT QUALITY AND PRICE ON THE INTEREST IN BUYING SCARLETT WHITENING PRODUCTS IN BEKASI - Sari, Cindy Antika; Sari, Imelda (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
The beauty product business has become increasingly attractive lately. This business has the potential to generate profits in the long term, especially if the target market feels the product is suitable. Beauty products are now spread in various types, with different purposes and levels of use, as well as the many ways that business people use to make their products known to the public. This incident certainly encouraged researchers to conduct research aimed at finding out what influences attract consumers to purchase a product. The variables used are brand ambassador, product quality and price on purchasing interest. Data was obtained from the results of an online questionnaire via Google form to 100 respondents using Scarlett Whitening products in Bekasi. Data analysis used IBM SPSS Statistics version 25 software with quantitative research methods. The research results reveal that brand ambassadors influence purchasing interest, then price also influences purchasing interest, while product quality has no influence on purchasing interest.